Strengthening and restoration of damaged reinforced concrete structures with composite plastics - Mukhanbetzhanova, Zhanna; Bespayev, Aliy (Eastern-European Journal of Enterprise Technologies, 2022)
This paper considers directions to devise methods for restoring the operational suitability of reinforced concrete structures. Mistakes of designers and non-compliance with the concreting technology of monolithic reinforced concrete structures lead to the formation of cracks and deflections of unacceptable size in reinforced concrete beams and floor slabs, as well as to insufficient strength of the elements. Such structures require not only an increase in bearing capacity but also the restoration of the operational suitability of damaged structures. A technique for restoring the serviceability of bendable reinforced concrete structures with increased deflections and excessive crack opening is proposed. To restore bendable reinforced concrete structures, surface reinforcement with pre-stressed fiber-reinforced plastics is suggested, which is ensured by the creation of a building lift in the damaged elements. Fiber-reinforced plastics have a high strain modulus, elastic nature of the diagram, and increased frost resistance; they tolerate fatigue effects well and are resistant to the effects of chemically active substances. Unlike conventional reinforcement methods, surface reinforcement techniques are characterized by high gain efficiency, corrosion resistance, low labor intensity, and short terms of work; they ensure strength increase and provide for economic feasibility. This study's results established that the use of fiber-reinforced plastics not only increases the bearing capacity of reinforced concrete structures but also helps reduce the width of the cracks formed. Thus, it is possible to avoid an increase in the cross-section of structures and reduce the time of operations, which could lead to additional costs